Review of Duodenoscope Infection Prevention Practices at the Medical University of South Carolina. (November 2020) - Ellison, Parker L.; Freeman, Janice; Elmunzer, B. Joseph; Cote, Gregory A.; Brock, Andrew S.
Abstract : A rise in duodenoscope-associated infections, especially in regard to multidrug-resistant organisms, has led to an increase in scrutiny regarding duodenoscope reprocessing. Endoscopic retrograde cholangiopancreatography scopes have a specialized elevator wire channel, allowing more flexible duct cannulation; however, this channel can be difficult to reprocess with standard techniques. Although strict adherence to manufacturer reprocessing protocols remains the primary means of infection prevention, periodic microbiological surveillance is a Food and Drug Administration-recommended practice that the Medical University of South Carolina has implemented to further prevent duodenoscope-associated infections. The Medical University of South Carolina obtains 2 separate cultures from 2 duodenoscopes every 2 months, which undergo standard speciation and sensitivity and are returned to use once negative at 48 hours. The initial results of the Medical University of South Carolina's surveillance cultures are negative for any multidrug-resistant organisms; however, other centers should consider implementing surveillance cultures into their reprocessing practices and closely monitoring for future endoscope infection prevention modalities.